Balancing the Interests of Parties in Contractual Relationship: How Fair is the Nigerian Petroleum Tax System to the State and the Oil Majors? - Kyari, Adam Konto (International Journal of Energy Economics and Policy, 2019)
Securing a fair share of oil wealth to the host government at the same time providing adequate incentives to the oil majors are two objectives that underpin the design of a fair petroleum tax system. These objectives are competing rather than complementing and thus the need for compromise by both the government and the oil majors to achieve fair contractual relationship. This study investigates whether the Nigerian petroleum tax system has fairly captured the interests of both the government and the oil majors. Guided by the economic rent theory, the study revealed, among others, that the tax system was fair in securing the government its fair share of oil wealth. Similarly, the tax incentives to the oil majors were adequate in positively influencing their investment decisions. The study concludes that the Nigerian petroleum tax has fairly captured the interests of both the government and that of the oil majors. Keywords: petroleum, fair, tax JEL Classifications: F21, H21